Wood Science for Conservation of Cultural Heritage - Braga 2008 Proceedings of the International Conference held by COST Action IE0601 (Braga - Portugal, 5-7 November 2008 - Gril, Joseph (Proceedings e report, 2010)
COST Action IE0601 "Wood Science for Conservation of Cultural Heritage" (www.woodculther.org) aims to improve the conservation of European wooden cultural heritage objects, by fostering research and interaction between researchers in various fields of wood science, conservators of wooden artworks, scientists from related fields. These proceedings contain the papers presented in the 2nd International Conference held in Braga (Portugal) 5-7/11/2008, dealing with themes such as material properties, biological degradation, characterization and measurement techniques, conservation, structures. This conference was patronized by the European Society for Wood Mechanics (ESWM), an informal body promoting wood mechanics in Europe by regular organisation of meetings through running COST Actions.